Inflation Expectations and Monetary Policy in India : An Empirical Exploration - Patra, Michael (IMF Working Papers; Working Paper, 2010)
This paper pursues a computationally intensive approach to generate future inflation, followed by an exploration of the determinants of inflation expectations by estimating a new Keynesian type Phillips curve that takes into account country-specific characteristics, the stance of monetary and fiscal policies, marginal costs and exogenous supply shocks. The empirical results indicate that high and climbing inflation could easily seep into people's anticipation of future inflation and linger. There is a reputational bonus for monetary policy to act against inflation now rather than going for cold turkey when societal compulsions reach a critical mass.